Water and salt balance at irrigation scheme scale: a comprehensive approach for salinity assessment in a Saharan oasis - Marlet, S.; Bouksila, F.; Bahri, Akissa (Elsevier, 2009)
Salt balance methods are generally applied in the root-zone and at local scales but do not provide relevant information for salinity management at irrigation scheme scales, where there are methodological impediments. A simple salt balance model was developed at irrigation scheme and yearly time scales and applied in Fatnassa oasis (Nefzaoua, Tunisia). It accounts for input by irrigation, export by drainage and groundwater flow, and provides novel computation of the influence of biogeochemical processes and variations in the resident amount of salt for each chemical component in the soil and shallow groundwater. Impediments were overcome by limiting the depth of the system so that the resident amount of salt that remained was of the same order of magnitude as salt inputs and allowed indirect and reliable estimation of groundwater flow. Sensitivity analyses as partial derivatives of groundwater salinity were carried out according to non-reactive salt balance under steady-state assumption. These analyses enabled the magnitude of the salinization process to be foreseen as a function of hydrological changes linked to irrigation, drainage, groundwater flow and extension of the irrigated area. From a salt input of 39 Mg ha1 year1 by irrigation, 21 Mg ha1 year1 (54%) and 10 Mg ha1 year1 (26%) were exported by groundwater flow and drainage, respectively. 7Mg ha1 year1 (18%) were removed from groundwater by geochemical processes, while a non significant 2 Mg ha1 year1 were estimated to have been stored in the soil and shallow groundwater where the residence time was only 2.7 years. The leaching efficiency of drainage was estimated at 0.77. With a water supply of 1360 mm by irrigation and 90 mm by rainfall, drainage, groundwater flow and actual evapotranspiration were 130, 230, and 1090 mm, respectively. The current extension of date palm plantations and salinization of groundwater resources are expected to significantly increase the salinity hazard while the degradation of the drainage system is expected to be of lesser impact. The approach was successfully implemented in Fatnassa oasis and proved to be particularly relevant in small or medium irrigation schemes where groundwater fluxes are significant.